High Seas to High Explosives: The Evolution of Calcaneus Fracture Management in the Military. Issue 11 (1st November 2014) - Balazs, George C.; Polfer, Elizabeth M.; Brelin, Alaina M.; Gordon, Wade T.
ABSTRACT: Calcaneus fractures typically occur as a consequence of axial load. In the civilian population, this is most often because of motor vehicle accidents or falls from height. Early management of these injuries in the military population largely mirrored that of civilian surgeons. However, calcaneus fractures secondary to underfoot blasts became a significant source of morbidity and mortality in World War II. First described in the aftermath of large-scale naval battles between metal-deck ships, this "deck-slap" phenomenon is associated with high rates of concomitant injuries, infection, and amputation. We review the historical and contemporary management of calcaneus fractures by military orthopedic surgeons, as well as detailing the unique challenges faced in managing the soft-tissue component and associated injuries commonly observed in this population. Combat-related calcaneus fractures are associated with very high rates of concomitant injuries and extensive soft-tissue wounds. Despite significant research and technological advances, functional outcomes following these devastating injuries have remained unsatisfying.